Synthesis of Ugi-4CR boronate analogues via microwave irradiation - Hsiao, Chao-Yu; Huang, Shi-Qing; Lien, Wan-Hsing; Hsu, Chen-Yun; Hsieh, Kun-lin; Lin, Meng-Hsuan; Wu, Meng-Ju; Fu, Chia-Chieh; Chen, Hsien-Chi; Fang, Hao-Ping; Li, Chia-Jung; Pan, Po-Shen (Research on chemical intermediates, 2017)
The synthetic condition for the synthesis of boronate ester Ugi-4CR analogs under mild conditions was developed. The reported reactions were carried out in methanol and promoted by microwave heating. This synthetic strategy could provide unique access to a broad range of boron-containing chemical libraries.